Jejak Periode Islam di Pesisir Barat Mamuju dan Mamuju Tengah, Provinsi Sulawesi Barat - Nani Somba; Syahruddin Mansyur; Chalid AS (Balai Arkeologi Provinsi Sulawesi Utara, 2020)
Archaeological studies examining the period of Islamic history in Mamuju and Central Mamuju to date are still minimal, on the other side geographically close to the center of the spread of Islam in West Sulawesi, Majene. This research is focused on the cultural footprint and distribution of archeological sites of the Islamic period in the Mamuju region. Archaeological survey methods and historical analysis are used to obtain a picture of the traces of Islamic culture at the study site. The traces of Islamic culture illustrate the interrelationship of the Mandar world cultural unity that is reflected through the form of tombs, gravestones, and old mosques in Mamuju. The traces of Islamic culture in the form of old mosques provide information about old toponymy and the process of spreading Islam in Mamuju that continued until the 19/20th century.